Boy - Bīto, Takeshi 1947- (Vertical, 2007)
A collection of three short stories features two brothers at a school sports day, another pair of brothers who use astronomy to cope with the loss of their father, and an uncool teenage boy who meets a biker girl in Kyoto
"Originally published in Japanese as Shonen by Shinchosha, Tokyo, 1987"--T.p. verso
Champion in a padded kimono -- Nest of stars -- Okamesan
Keywords: Bito Takeshi / Translations into English; Bīto Takeshi -- Translations into English; Short stories